(907) Evaluation of Social Action Programs تقييم برامج العمل الاجتماعي - W. A. Hassouna. (INP, 2024)
This study discusses the evaluation of social action programs conducted in his capacity as an evaluator for the Pittsburgh Board of Public Education. Each of the two programs illustrates a special aspect of evaluation. These case studies should be read in light of certain research principles that are crucial in any type of evaluation, which can be framed as questions the evaluator must ask: (1) What is the nature of the program being evaluated? (2) What variable(s) is(are) being regulated by the social action program or should be regulated? (3) What are the formal and informal objectives of the program under evaluation? (4) To what extent is the program actually accomplishing the stated objectives? To answer these questions, the evaluator must develop a means of analyzing the social action program.